(3EjVGM GdeOGQc aj GdEaUGM Yf GdYhGJcs - (3eQJVj GdRHjOj , eMeO Hf eMeO Hf eMeO Hf YHO GdQRGb GdMSjfj, CHh GdajV,J (B1205 (3g` s ((3eMeO CHhGdfUQ gGTe GdLYaQj GdfGHdSj s)
(3ChdgG (B:s
(3CeG HYO agPg fHPI MLegG UZjQ hdcf faYgG Ef TGA Gddg cKjQ, JJVef HjGf CegGJgG Udi Gddg Ydjg hSde ef GdYhGJc ef Hfi Sdje hZjQge s
(3BNQgG (B:s
(3bGd eDdag(B: (3aQZ ef JMQjQ gPg GdCSWQ egPHgG aj jhe GdMO GQHY eVjf ef QHjY GdKGfj SfI (B1194(3g` s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B20s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B282s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B398 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B57 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs